2023
DOI: 10.1039/d3qm00089c
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in transition metal-based MOFs for electrocatalytic water splitting emphasizing fundamental and structural aspects

Abstract: Energy scarcity and environmental pollution are major threats to the long-term viability of the modern civilization. Electrocatalytic water splitting is a crucial technology for environmentally friendly and long-lasting energy storage...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 108 publications
0
27
0
Order By: Relevance
“…148 Lin et al also prepared hollow porous carbon in cages co-doped with Co and N via zeolitic imidazolium salt framework (ZIF)-triggered rapid polymerization of dopamine for efficient ORR and OER electrocatalysts. 149 Even though MOFs and COFs with unique structures and properties have been investigated as efficient electrocatalysts for oxygen evolution reaction (OER), hydrogen evolution reaction (HER), oxygen reduction reaction (ORR), CO 2 reduction reaction (CO 2 RR), selective oxidation of organics, etc., [150][151][152][153] the MOF/COF composites have been rarely reported as electrocatalysts.…”
Section: Electrocatalytic Applicationsmentioning
confidence: 99%
“…148 Lin et al also prepared hollow porous carbon in cages co-doped with Co and N via zeolitic imidazolium salt framework (ZIF)-triggered rapid polymerization of dopamine for efficient ORR and OER electrocatalysts. 149 Even though MOFs and COFs with unique structures and properties have been investigated as efficient electrocatalysts for oxygen evolution reaction (OER), hydrogen evolution reaction (HER), oxygen reduction reaction (ORR), CO 2 reduction reaction (CO 2 RR), selective oxidation of organics, etc., [150][151][152][153] the MOF/COF composites have been rarely reported as electrocatalysts.…”
Section: Electrocatalytic Applicationsmentioning
confidence: 99%
“…This approach achieves its efficacy by manipulating different aspects of the material structures such as surface free energy, surface vacancies, formation of hetero/homojunctions, effective mass of holes/ electrons, and loading of cocatalyst sites, among others. 3,21 Primarily, PE focuses on exploring unconventional phases, heterophase structures, and phase transitions. 22 Traditionally, nanomaterials adopt thermodynamically stable phases as their bulk counterparts.…”
Section: Qi Shenmentioning
confidence: 99%
“…1,2 Hydrogen, a well-known clean energy source, is widely recognized as an ideal alternative to traditional fossil fuels due to its high energy density (i.e., 120 MJ kg À1 versus gasoline 42.86 MJ kg À1 ). [2][3][4] In comparison with traditional energy development technologies, sustainable hydrogen production by water splitting has enhanced environmental and economic effectiveness. 5 In a common three-electrode electrolytic system, electrochemical water splitting includes two parts: HER and OER.…”
Section: Introductionmentioning
confidence: 99%
“…The host layer consists of mainly the active sites which are made of edge-sharing octahedral MO 6 units . Among the transition metals, particularly, Co-, Fe-, and Ni-based LDH materials are the most assuring metals for water electrolysis, although they have a less conductive nature due to their semiconducting or insulating nature, which affects the electron transfer process. Again, in particular, recent research demonstrated that a CoFe-based LDH in alkaline electrolytes exhibits enhanced OER performance due to its strong synergistic effect between Fe and Co ions, creating a favorable electronic structure and local coordination atmosphere. Here also, the working of the CoFe-LDH is still limited by its sluggish water dissociation process and low electrically conductive nature. , However, for practical application, an increase in the catalytic efficiency of this electrocatalyst was very much needed.…”
Section: Introductionmentioning
confidence: 99%